Characterization of Terephthalic Acid Monomer Recycled from Post‐Consumer PET Polymer Bottles. Issue 1 (29th March 2016) - Ravichandran, Sankaranarayanan Ayyakudi; Rajan, Vignesh Peranamallur; Aravind, Pritham Velamur; Seenivasan, A.; Prakash, D. Gnana; Ramakrishnan, K.
Summary: The idea of recycling of PET to obtain terephthalic acid (TPH) monomer is fast gaining traction; therefore it has become imperative to develop standard characterization methods to assess the purity of terephthalic acid using reliable and easily available laboratory equipment/techniques. Experimental studies on recycling of post‐consumer PET waste were conducted in a batch reactor. The PET was subjected to a de‐esterification reaction to break down the ester bonds via alkali decomposition in ethylene glycol at 155 °C under the influence of ultrasound. The end product, terephthalic acid, was characterized for the functional purity using UV‐Visible spectrophotometry, FT‐IR, and thermal methods. The terephthalic acid was ascertained by the characteristic peak at 240 nm using UV‐Visible spectrophotometer and was quantified using a commercially available standard sample of terephthalic acid. The purity of end product was confirmed using FT‐IR and thermogravimetric and differential thermal analysis.